Controlling Complex Multimedia Systems via Reflection and Ontologies - Daniel Oancea (2009)
Multimedia distributed services are complex systems and become to play an important role in many human activities over the past few years. As computer and communication technologies evolve, there is an increasing demand for multimedia applications capable to deliver to end-users, the right content with the right format at the right moment. To achieve this, the components that form the system must be initially configured and, possibly, later on adapted to cope with changes in network conditions, users preferences and environment settings. Over the past years, research on multimedia systems adaptation evolved from scattered approaches into integrated ones by combining information from several layers of the OSI stack. This position paper proposes a novel cross-layer design approach for managing adaptation in multimedia distributed systems by combining ontologies and reflection.